Neuropathic pain after chronic nerve constriction may not correlate with chloride dysregulation in mouse trigeminal nucleus caudalis neurons. Issue 7 (July 2017) - Castro, Alberto; Li, Ying; Raver, Charles; Chandra, Ramesh; Masri, Radi; Lobo, Mary K.; Keller, Asaf
Abstract : Abstract: Changes in chloride reversal potential in rat spinal cord neurons have previously been associated with persistent pain in nerve injury and inflammation models. These changes correlate with a decrease in the expression of the potassium chloride transporter, KCC2, and with increases in neuronal excitability. Here, we test the hypothesis that similar changes occur in mice with neuropathic pain induced by chronic constriction injury of the trigeminal infraorbital nerve (CCI-ION). This model allows us to distinguish an acute pain phase (3-5 days after injury) from a persistent pain phase (12-14 days after CCI-ION). Chronic constriction injury of the trigeminal infraorbital nerve induced significant decreases in mechanical pain thresholds in both the acute and persistent phases. To estimate GABAA reversal potentials in neurons from trigeminal nucleus caudalis, we obtained perforated patch recordings in vitro. GABAA reversal potential decreased by 8% during the acute phase in unidentified neurons, but not in GABAergic interneurons. However, at 12 to 14 days after CCI-ION, GABAA reversal potential recovered to normal values. Quantitative real-time polymerase chain reaction analysis revealed no significant changes, at either 3 to 5 days or 12 to 14 days after CCI-ION, in either KCC2 or NKCC1. These findings suggest that CCI-ION in mice results in transient and modest changes in chloride reversal potentials, and that these changes may not persist during the late phase. This suggests that, in the mouse model of CCI-ION, chloride dysregulation may not have a prominent role in the central mechanisms leading to the maintenance of chronic pain. Abstract : Chronic neuropathic pain was not associated with hypothesized, permanent chloride dysregulation or in the expression of chloride transporters.